Cruise Control Study: Simplification of IVF Monitoring in a Mixed Protocol Using a Novel Dosing Regimen - Benguigui, Jonas; Kadoch, Eva; Bannan, Amro; Phillips, Simon; Hemmings, Robert; Bissonnette, François; Kadoch, Isaac-Jacques (Archives of Clinical and Biomedical Research, 2024)
Objective: To identify the subset of the in vitro fertilization (IVF) population suitable for minimal monitoring by implementing a novel dosing regimen. Methods: A retrospective study conducted between April 2021 and August 2022. Eligible participants were aged 18 or older, had undergone IVF stimulation using an antagonist protocol, and were prescribed a combination of follitropin delta and human menopausal gonadotropin. The dosage was either based on a patient-specific dosing regimen developed by the ovo clinic utilizing weight and AMH levels (Group 1, n=356) or determined through clinical evaluation by the physician (Group 2, n=358). On day 6, ultrasound and serum hormone analyses were performed, with adjustments made solely to the menotropin dosage in necessary. Results: The study enrolled a total of 714 patients. In Group 1, 80, 3% of patients were stimulated at maximal doses compared to 14, 5% in Group 2. No cases of moderate or severe cases of ovarian hyperstimulation syndrome (OHSS) were recorded. The frequency of dose adjustments before day 10 was minimal. Patients treated with non-maximal doses according to the dosing regimen showed significantly fewer adjustments on day 6 compared to those treated according to physician's assessment (24.6% versus 46.9%, p<0.001). Among this subgroup, OHSS risk was observed in 30.4% of cases. Conclusion: Our innovative dosing regimen suggests that initial monitoring on day 10 would suffice for IVF patients with low ovarian reserve undergoing maximal stimulation.